The Responsibility Of Pt Kereta Api Indonesia Due To Crossing Accidents From The Perspective Of Maqashid Syariah (Case Study Of The Padang Road Railway Crossing, Medan Tembung) - Desi Anggraini; Rahmad Efendi (UNIVERSITAS PAKUAN, 2024)
This research examines the accountability of PT Kereta Api Indonesia (KAI) for accident victims at level crossings without barriers from the perspective of Maqashid Syariah, with a case study on Jalan Padang, Medan Tembung. The purpose of this research is to identify the factors causing accidents, formulate solutions to reduce the accident rate, and analyze the accountability of PT Kereta Api Indonesia (PT KAI) towards the victims from the perspective of Maqashid Syariah. This research uses qualitative methods, and the type of research is empirical juridical with a case approach, legislative approach, and conceptual approach. The research results show that PT KAI cannot be held directly responsible for accidents at level crossings without gates because the responsibility for installing gates and regulating level crossings lies with the government according to road class. Factors that cause the absence of gates at all level crossings include budget limitations, the large number of crossings, the complexity of installation authority, and the lack of public awareness. Solutions to reduce accidents at level crossings include public outreach, closing unofficial crossings, installing concrete barriers to block vehicles, and regular evaluation and supervision by the government. From the perspective of Maqashid Syariah, particularly the principle of preserving life (Hifzhu An-Nafs), PT. KAI still has a moral responsibility to assist accident victims by helping with insurance claims for accident victims, enhancing security, and educating the public, even though it is not directly responsible for the installation of crossing gates. This research concludes the need for cooperation between PT KAI, the government, and the community to improve safety at level crossings.Keywords: Accountability, Accident, train, Level Crossing, Maqashid Shariah